Case report: Successful percutaneous extracorporeal magnetic levitation ventricular assist device support in a patient with left heart failure due to dilated cardiomyopathy - Li, Ping; Zhang, Xiaoying; Chen, Shu; Hsu, Po-lin; Wu, Tingting; Qian, Shirui; Su, Wei; Wang, Guohua; Dong, Nianguo (Frontiers in Cardiovascular Medicine, 2023)
Abstract Induction: Mechanical circulatory support (MCS) can help to maintain hemodynamic stability, improve cardiac function, reduce cardiac load, and is an important method for the treatment of advanced heart failure. However, traditional MCS systems (IABP, Impella, TandemHerat, veno‐arterial extracorporeal membrane oxygenation [VA-ECMO]) are associated with limitations including trauma, a high rate of complications (hemolysis, bleeding) and require complex care from nurses. Case summary: We report a case of left heart failure resulting from dilated cardiomyopathy in a 24-year-old man. A catheter was placed through the right jugular vein and a drainage tube was positioned under ultrasound guidance through the superior vena cava, right atrium, atrial septum, to the left atrium, and returned to the axillary artery using an extracorporeal magnetic levitation ventricular assist device (VAD). The patient was successfully supported for 10 days and bridged to heart transplant. Discussion: To the best of our knowledge, this is the first report of the use of an extracorporeal magnetic levitation VAD for MCS via a percutaneous approach. Our findings support the wider use of this strategy for patients awaiting myocardial recovery or who require heart bridging or transplantation.